The Effect of Green Banking and Risk Management on Profitability with ESG Disclosure as a Moderation - Wirawan Widjanarko; Wastam Wahyu Hidayat; Yoseph Anastasius Didik Cahyanto (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The increasing importance of sustainable finance and the growing role of environmental, social, and governance practices in shaping banking performance. This study examines the impact of green banking, risk management, and ESG disclosure on bank profitability, with ESG disclosure also tested as a moderating variable.  A quantitative approach with a causal associative design is applied using data from banking companies listed on the Indonesia Stock Exchange during 2023–2025. Multiple regression analysis is employed to test both direct and moderating effects. The findings show that green banking and ESG disclosure have a positive and significant effect on profitability, while risk management, proxied by non-performing loans, has a significant negative effect. Furthermore, ESG disclosure strengthens the relationship between green banking and profitability and moderates the effect of risk management by reducing the adverse impact of credit risk on financial performance. The results indicate that sustainability-oriented practices combined with effective risk management play a crucial role in improving banking profitability. The study concludes that integrating green banking initiatives with strong ESG disclosure practices enhances financial outcomes, while proper risk control remains essential for maintaining stability and long-term performance in the banking sector.